A new mechanical stellar wind feedback model for the Rosette Nebula. Issue 3 (13th February 2018) - Wareing, C J; Pittard, J M; Wright, N J; Falle, S A E G
Abstract: The famous Rosette Nebula has an evacuated central cavity formed from the stellar winds ejected from the 2–6 Myr old codistant and comoving central star cluster NGC 2244. However, with upper age estimates of less than 110 000 yr, the central cavity is too young compared to NGC 2244 and existing models do not reproduce its properties. A new proper motion study herein using Gaia data reveals the ejection of the most massive star in the Rosette, HD 46223, from NGC 2244 occurred 1.73 (+0.34, −0.25) Myr (1σ uncertainty) in the past. Assuming this ejection was at the birth of the most massive stars in NGC 2244, including the dominant centrally positioned HD 46150, the age is set for the famous ionized region at more than 10 times that derived for the cavity. Here, we are able to reproduce the structure of the Rosette Nebula, through simulation of mechanical stellar feedback from a 40 M⊙ star in a thin sheet-like molecular cloud. We form the 135 000 M⊙ cloud from thermally unstable diffuse interstellar medium (ISM) under the influence of a realistic background magnetic field with thermal/magnetic pressure equilibrium. Properties derived from a snapshot of the simulation at 1.5 Myr, including cavity size, stellar age, magnetic field, and resulting inclination to the line of sight, match those derived from observations. An elegant explanation is thus provided for the stark contrast in age estimates based on realistic diffuse ISM properties, molecular cloud formation and stellar wind feedback.